2022
DOI: 10.1177/03913988221108754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between health literacy and self-efficacy: A sample of hemodialysis patients

Abstract: Purpose: The aim of this study was to evaluate self-efficacy and health literacy of patients undergoing hemodialysis, to investigate the relationship between health literacy and self-efficacy, and to determine the factors affecting self-efficacy. Methods: The study was conducted in Eskisehir and Gumushane state hospitals affiliated to the Public Hospitals Association with the participation of 198 patients receiving hemodialysis treatment for chronic renal failure. The inclusion criteria were as follows: being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…Participants in the high and moderate HL profiles displayed greater levels of self-efficacy in fluid management compared to those in the low HL profile. These findings align with previous studies documenting that higher HL scores were associated with increased self-efficacy in individuals receiving haemodialysis (Kazak et al, 2022;Lim et al, 2020). We found that participants exhibited moderate self-efficacy levels (M = 3.74, SD = .81), which were slightly lower than those observed in the samples from the The SEM results provided partial support for our hypothesized model, suggesting that participants in the high HL profile were less likely to adopt traditional dietary habits than those in the low profile.…”
Section: Discussionsupporting
confidence: 92%
“…Participants in the high and moderate HL profiles displayed greater levels of self-efficacy in fluid management compared to those in the low HL profile. These findings align with previous studies documenting that higher HL scores were associated with increased self-efficacy in individuals receiving haemodialysis (Kazak et al, 2022;Lim et al, 2020). We found that participants exhibited moderate self-efficacy levels (M = 3.74, SD = .81), which were slightly lower than those observed in the samples from the The SEM results provided partial support for our hypothesized model, suggesting that participants in the high HL profile were less likely to adopt traditional dietary habits than those in the low profile.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, patients can better apply their knowledge when making health-related decisions and potential problems can be minimized. In the literature review, although studies with chronic kidney disease [21] and hemodialysis patients in Turkey were published [22,23], studies on health literacy in older adults receiving hemodialysis treatment is lacking. The aim of this study was to determine the health literacy levels and related factors of older adults receiving hemodialysis treatment.…”
Section: Introductionmentioning
confidence: 99%